Primary hyperparathyroidism and incidental multifocal metastatic papillary thyroid carcinoma in a man - Polyzos,Stergios A. (2010)
Co-existence of primary hyperparathyroidism (PHPT) and non-medullary thyroid carcinoma has been previously reported in sporadic case reports and some surgical series, but the majority of cases concerned women with occult papillary carcinomas without cervical lymph node involvement. We present a 71-year man with PHPT and multinodular goiter who was subjected to surgery for single parathyroid adenoma and was found to have synchronous multifocal papillary thyroid carcinoma (PTC) with cervical lymph node involvement. Review of the literature retrieved only a few similar cases. Ultrasonography of both thyroid and parathyroid glands might be considered in patients with hyperparathyroidism. Given that there are no specific guidelines for the management of patients with synchronous PHPT and PTC, they should be managed like the cases of single PTC.